Ways to expand the worldview and develop it psychologically and scientifically through language learning (Journal of Science-Innovative Research in Uzbekistan, 2024)
At a time when the world is developing, people's thoughts about critical thinking are also becoming more positive. Yes, there is no development without critical thinking. It works out much better. This should be included in the education system as a subject. In this theme, foreign countries are well ahead of us. So that, we should learn also languages of the most developed countries. In this essay, you will learn about the benefits of critical thinking, how it has proven to work in foreign countries, and how you can advance through critical thinking. Critical thinking makes a great positive contribution to global development, of course. In addition, critical thinking develops other skills in a person.